The Myth of Gyges’ Ring in Plato’s Republic - Higuera Linares, María Marcela; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2016)
This article inquires into the second book of Plato’s Republic, where Glaucon tells the myth of Gyges’ ring, drawing the limit for a corrupt notion of justice. This narration allows the radical emergence of the main problem in the dialogue. Multiple images serve to build a distinct scene that alludes to the universal question of mankind’s capacity of choice. Issues regarding history, politics and economics are present, with allusions to the work of Archilocus and Herodotus. In this context, the myth represents an explicit invitation to recognize the responsibility of choice, always concerning life in a community and the possibility of attaining different media to modify the appearance of this presence.